Specific roles of GABA(B(1)) receptor isoforms in cognition - Jacobson, Laura H. (2007)
The GABA(B) receptor is a heterodimer of GABA(B(1)) and GABA(B(2)) subunits. There are two isoforms of the GABA(B(1)) subunit: GABA(B(1a)) and GABA(B(1b)). Recent studies with mutant mice suggest a differential role for the two GABA(B(1)) isoforms in behavioural processes. As pharmacological and genetic studies have implicated GABA(B) receptors in cognition we investigated the behaviour of GABA(B(1a)) (−/−) and GABA(B(1b)) (−/−) mice in different types of cognitive paradigms. GABA(B(1a)) (−/−) and GABA(B(1b)) (−/−) mice were both impaired relative to wildtype controls in a continuous spontaneous alternation behaviour test of working spatial memory. In contrast to the reported phenotype of GABA(B(1)) (−/−) mice, however, neither GABA(B(1a)) (−/−) nor GABA(B(1b)) (−/−) mice were deficient in a passive avoidance task. On the other hand, GABA(B(1a)) (−/−) mice were impaired in familiar and novel object recognition. We conclude that GABA(B(1)) isoforms contribute differentially to GABA(B) receptor-mediated cognitive processes.